Determination of total flavonoids in three Sedum crude drugs by UV–Vis spectrophotometry - Chen, Yujie (Medknow Publications, 2010)
A simple, rapid UV–Vis spectrophotometry method for the determination of total flavonoids in Sedum sarmentosum Bunge., S. lineare Thunb., and S. erythrostictum Migo. was developed, with a good linearity, precision, and stability. The detection wavelength was set at 500 nm, and an extraction solvent was optimized. Through the comparative study of multiple samples of the three plant drugs, their collected seasons and the habitats can be preliminarily ascertained, which may help to control the quality of the medicines to some extent.